2018
DOI: 10.1021/jacs.8b00885
|View full text |Cite
|
Sign up to set email alerts
|

Localized Symmetry Breaking for Tuning Thermal Expansion in ScF3 Nanoscale Frameworks

Abstract: The local symmetry, beyond the averaged crystallographic structure, tends to bring unusual performances. Negative thermal expansion is a peculiar physical property of solids. Here, we report the delicate design of the localized symmetry breaking to achieve controllable thermal expansion in ScF nanoscale frameworks. Intriguingly, an isotropic zero thermal expansion is concurrently engineered by localized symmetry breaking, with a remarkably low coefficient of thermal expansion of about +4.0 × 10/K up to 675 K. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 28 publications
(22 reference statements)
0
35
0
Order By: Relevance
“…PDF is a powerful technique, which could be used to analyze local structures in functional materials. [ 34 ] The first peak in G( r ) function located around 2–3 Å is assigned to the nearest neighboring MSe bonds (M = Cu/Ag/Sn/Ga/Na), as shown by the green circle in Figure 6 a. In the cubic AgGaNa3, all MSe bond should be identical due to crystallographic symmetry constrain.…”
Section: Resultsmentioning
confidence: 99%
“…PDF is a powerful technique, which could be used to analyze local structures in functional materials. [ 34 ] The first peak in G( r ) function located around 2–3 Å is assigned to the nearest neighboring MSe bonds (M = Cu/Ag/Sn/Ga/Na), as shown by the green circle in Figure 6 a. In the cubic AgGaNa3, all MSe bond should be identical due to crystallographic symmetry constrain.…”
Section: Resultsmentioning
confidence: 99%
“…85 Furthermore, it was recently shown that the degree of NTE in ScF 3 is particle size dependent, 96 and can actually be tuned between NTE, zero thermal expansion (ZTE), and PTE, by nanostructuring the product. 97 The tunability has been ascribed to local symmetry breaking as the particle size is decreased, i.e. the local structure is rhombodrally distorted (as evi- Figure 4: Lattice constant versus temperature (log scale).…”
Section: Inorganicsmentioning
confidence: 99%
“…We collected total neutron scattering data from a powder sample of scandium trifluoride, measuring both the Bragg scattering-sensitive to the long-range order-and the diffuse scattering. Although several previous pair distribution function studies of ScF 3 have used x-rays [15,[27][28][29], for our analysis neutron radiation was a more appropriate choice, for three reasons. First, the accessible range of scattering vector Q, and hence the resolution of the pair distribution function derived from it, is much greater: we were able to measure up to a maximum value of Q max = 50 Å −1 , while with x rays the maximum achievable value of Q with a short-wavelength silver anode is 22.5 Å −1 and is usually practically up to around 30 Å −1 with synchrotron radiation measurements.…”
Section: Real-space Analysis Of Negative Thermal Expansionmentioning
confidence: 99%